Fração de filme líquido nas paredes de um lavador Venturi - Daher, Maristela de Almeida Felício (Universidade Federal de São Carlos, 2008)
The study of the liquid film in the walls of a Venturi scrubber was chosen as the target of this work for representing one of the important phenomena that influence the collection efficiency of the equipment. Such efficiency decreases with the presence of the film once it has a superficial area per volume much smaller than the drops and, consequently, contributes very little in the removal of particles. Furthermore, the pressure drop on the Venturi depends on the energy spent to accelerate the drops and also of the attrition between the gas and the surface of the film. These two important parameters depend on the liquid fraction in the form of film. For these reasons, it is important for the project of Venturi scrubbers the quantification of the film fraction. The present work, therefore, carried out an experimental investigation of the effects that the liquid injection through multiple jets exerted in the formation of the liquid film in a Venturi scrubber of rectangular cross section. The behavior of the fraction of liquid film in each wall separately and of the total fraction of liquid film extracted were analyzed, varying the liquid flow rate from 0,3 to 1,2 l/min for gas velocities of 59, 64, 69 and 74 m/s. Throat lengths of 100, 160 and 220 mm were utilized. The results showed that the film fraction varies with the gas velocity, with the configuration of the liquid injection, with the liquid flow rate and with the axial distances along the throat. The analysis of the film extraction in the individual walls follows an asymmetric behavior in all operational conditions, showing a larger film deposition in the inferior wall independently of the injection configuration, thus indicating the effect of the gravity in the film deposition. Hence, the total fraction of liquid extracted from the four walls of the scrubber made possible a more satisfactory interpretation of the results. Within the experimental range investigated, the injection through four orifices at the gas velocity of 74 m/s at the higher liquid flow rates presented the smaller deposition of liquid in the scrubber walls. It was also evident that the deposition is dependent on the penetration of the jet: low penetrations tend to deposit in the jet injection wall while high penetrations deposit in the opposite wall. There is, therefore, a point of minimum deposition for the intermediate penetration of the jet. The best operational conditions, i.e. the smallest film fraction deposited in the walls, was obtained for the largest gas velocity and for the liquid being injected simultaneously through the four walls.
Keywords: Ar - poluição; Lavador Venturi; Coletas de partículas; Limpeza de gases industriais; Filme líquido; ENGENHARIAS::ENGENHARIA QUIMICA